2015
DOI: 10.1021/acs.analchem.5b00571
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Quantitation of Na+and K+in Single Normal and Cancer Cells Using a New Near-Infrared Fluorescent Probe

Abstract: Considering the important functions of cellular Na(+) and K(+) together with their cooperative efforts on various biological processes, it is significant to simultaneously detect Na(+) and K(+) at a single-cell level. Here, we present a novel method to discriminate and quantify simultaneously Na(+) and K(+) in single cells using a new near-infrared fluorescent probe associated with microchip electrophoresis. The fluorescent probe selectively responds to both Na(+) and K(+). The microchip electrophoresis allows… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
34
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(36 citation statements)
references
References 55 publications
1
34
0
1
Order By: Relevance
“…Looking for a more universal marker of necrosis, we mapped the relative abundance of sodium and potassium in the tissue, as previous studies have reported changes in the abundance of those adducts during cell apoptosis and cancer [26]. To determine the Na + /K + ratio it is necessary to find species whose adducts are free of other species interferences.…”
Section: Resultsmentioning
confidence: 99%
“…Looking for a more universal marker of necrosis, we mapped the relative abundance of sodium and potassium in the tissue, as previous studies have reported changes in the abundance of those adducts during cell apoptosis and cancer [26]. To determine the Na + /K + ratio it is necessary to find species whose adducts are free of other species interferences.…”
Section: Resultsmentioning
confidence: 99%
“…Near-infrared fluorescent probes are highly needful, because light in the NIR region shows lower background fluorescence, less phototoxicity, and deeper penetration [39][40][41][42][43][44][45][46][47][48]. Several fluorescence probes based on near-infrared dyes have been designed.…”
mentioning
confidence: 99%
“…the maintenance of the concentration gradient of ions across the cell membrane), which is strongly related to cellular metabolism, and has shown promise to detect malignancy and monitor NACT response. Previous studies showed that the total sodium concentration was significantly greater in malignant breast lesions (+50%‐60%) compared with healthy tissues, whereas distinct trends were observed in chemotherapy responders (−20%‐30%) compared with nonresponders (+5%‐10%) …”
Section: Introductionmentioning
confidence: 94%
“…the maintenance of the concentration gradient of ions across the cell membrane), which is strongly related to cellular metabolism, and has shown promise to detect malignancy and monitor NACT response. Previous studies showed that the total sodium concentration was significantly greater in malignant breast lesions (+50%-60%) compared with healthy tissues, [16][17][18] whereas distinct trends were observed in chemotherapy responders (−20%-30%) compared with nonresponders (+5%-10%). 19,20 Due to low sodium content in the body (approximately 15 mM inside the cells and 140 mM outside), its low MR sensitivity (9.27% that of hydrogen) and short transversal relaxation times in biological tissues (T 2,short = 1-5 ms, T 2,long = 10-60 ms), 23 Na MRI suffers from intrinsically low SNR, which can be approximately 20,000 times lower than that of proton.…”
Section: Introductionmentioning
confidence: 99%